Lemon aromatherapy for emesis gravidarum: A systematic review - Fitria Widyanto Putri, Herdian; Farokah, Atik; Khusmitha, Qatrunnada Naqiyyah (International Journal of Nursing and Midwifery Research, 2023)
Emesis gravidarum is a discomfort that is often experienced by pregnant women in the first trimester. If not treated properly, emesis gravidarum can turn into a worse condition, namely hyperemesis gravidarum. Hyperemesis gravidarum has a negative impact on the mother and fetus. One of the therapies that is currently trending is the use of lemon aromatherapy. This study aims to carry out a systematic review of lemon aromatherapy on the nausea and vomiting scale. A search for English articles was conducted at Willey, ScienceDirect, EBSCO Host, and Google Scholar for the 2018–2022 period. Based on the systematic review conducted, there were four articles that met the criteria. The majority of the articles were conducted with pregnant women in their first trimester. The majority of nausea and vomiting scale assessments used the PUQE. The duration for giving lemon aromatherapy varies: every day for 2 weeks, twice a day for 1 week, twice a day for 3 days, and is unknown. Giving lemon aromatherapy can reduce the scale of nausea and vomiting in pregnant women with emesis gravidarum.